(D-1)x + Dy = 0
Dx + 2Dy = 4"e^2t"
Let us solve the system:
"\\begin{cases}\n(D-1)x + Dy = 0\\\\\nDx + 2Dy = 4e^{2t}\n\\end{cases}"
"\\begin{cases}\nDy = -(D-1)x \\\\\nDx + 2Dy = 4e^{2t}\n\\end{cases}"
"\\begin{cases}\nDy = -(D-1)x \\\\\nDx - 2(D-1)x = 4e^{2t}\n\\end{cases}"
"\\begin{cases}\nDy = -(D-1)x \\\\\n-(D-2)x = 4e^{2t}\n\\end{cases}"
"\\begin{cases}\nDy = -(D-1)x \\\\\n(D-2)xe^{-2t} = -4\n\\end{cases}"
"\\begin{cases}\nDy = -(D-1)x \\\\\nD(xe^{-2t}) = -4\n\\end{cases}"
"\\begin{cases}\nDy = -(D-1)x \\\\\nxe^{-2t} = -4t+C_1\n\\end{cases}"
"\\begin{cases}\nDy = -(D-1)x \\\\\nx = -4te^{2t}+C_1e^{2t}\n\\end{cases}"
"\\begin{cases}\nDy = 4e^{2t}+8te^{2t}-2C_1e^{2t}-4te^{2t}+C_1e^{2t}= 4e^{2t}+4te^{2t}-C_1e^{2t}\\\\\nx = -4te^{2t}+C_1e^{2t}\n\\end{cases}"
We conclude that the solution is of the following form:
"\\begin{cases}\ny =e^{2t}+2te^{2t}-\\frac{1}{2}C_1e^{2t}+C_2\\\\\nx = -4te^{2t}+C_1e^{2t}\n\\end{cases}"
Comments
Leave a comment